Optimization of Production Processes to Minimize Waste and Improve Efficiency in Automobile Servicing Plant Using Lean Six Sigma - Amal R; Mrs. Maneesha PS; Premjith S; Mr Santhu Varghese Thomas (International Journal of Manufacturing and Production Engineering, 2024)
This study focuses on optimizing production processes within an automobile servicing plant to minimize waste and enhance efficiency through the application of lean six sigma (LSS) methodologies. Utilizing a case study approach, the research addresses real-time challenges related to productivity and waste reduction. Data collection involves assessing machine functionality metrics, material and labor flow at various stages of the servicing process. The optimization strategy integrates lean tools including value stream mapping, process cycle efficiency analysis, Kaizen practices, 5S methodology, and Pareto charting. Findings indicate opportunities for improvement, including suboptimal process cycle efficiency, inadequate takt time, prolonged lead times, and excessive downtime. Following the implementation of lean six sigma methodologies, significant enhancements are observed across all evaluated parameters. The study underscores the practical application of LSS principles in optimizing production processes within the automobile servicing industry, contributing valuable insights for enhancing operational efficiency and waste reduction. Further validation through lean-based software tools is recommended to reinforce the study's findings.
Keywords: lead time; lean manufacturing; process cycle efficiency; takt time; value added time